Text-Transforms – the Communicative Paradigm Basis of a Literary Work - Синявська, Леся Іванівна; Синявська, Л. І.; Синявская, Леся Иванована; Syniavska, Lesia I.; Колкутіна, Вікторія Вікторівна; Колкутіна, В. В.; Колкутина, Виктория Викторовна; Kolkutina, Viktoriia V.; Погребенник, Володимир Федорович; Погребенник, В. Ф.; Погребенник, Владимир Федорович; Pohrebennyk, Volodymyr F. (Khachatur Abovyan Armenian State Pedagogical University, 2020)
The article introduces and investigates the concept of a “text-transform” based on the novel and short-novel plots of the drama works of the Ukrainian dramatists of the late 19th – early 20th centuries. The text-transform is defined as a message by a different author, with a different structure, different code, composition, and fable, sometimes, with a different system of images. This research paper also looks at the differ-ent levels of transformations: dramatisation, adaptation, and creation of a play, based on a literary work. The early 20th century sees actualisation of the strategy of transformed communication, when in the process of transformation of the narrative elements, dramatists exploit the strategy of preservation, shortening, expanding, and changing text blocks. It is determined by the theatre-specific process and pragmatic orientation on the stage performance. Meanwhile, extension and changes that a text-reference is subject to are aimed to explicate and intensify the current and preserved relationships between characters in text-transforms.

Стаття представляє та досліджує концепцію «перетворення тексту», засновану на романі та короткометражних сюжетах драматичних творів українських драматургів кінця ХІХ - початку ХХ століття. Трансформація тексту визначається як повідомлення іншого автора, з іншою структурою, іншим кодом, композицією та байкою, іноді з іншою системою зображень. У цій роботі також розглядаються різні рівні трансформацій: театралізація, адаптація та створення п’єси за літературним твором. На початку 20 століття спостерігається актуалізація стратегії трансформованого спілкування, коли в процесі трансформації елементів розповіді драматурги використовують стратегію збереження, скорочення, розширення та зміни текстових блоків. Це відзначається специфічним для театру процесом та прагматичною спрямованістю на сценічній виставі.Тим часом розширення та зміни, яким підлягає текст-посилання, мають на меті пояснити та активізувати поточні та збережені взаємозв'язки між символами у перетворених текстах.

Статья представляет и исследует концепцию «преобразования текста», основанную на романе и короткометражных сюжетах драматических произведений украинских драматургов конца XIX - начала ХХ века. Трансформация текста определяется как сообщение другого автора, с другой структурой, другим кодом, композицией и байками, иногда с другой системой изображения. В этой работе можно посмотреть разные уровни трансформации: театрализация, адаптация и создание пьесы, основанной на литературном произведении. В начале 20 века наблюдается актуализация стратегии трансформированного общения, когда в процессе трансформации элементы повествования драматургии разрабатываются стратегия сохранения, сокращение, расширение и изменения текстовых блоков. Это отмечается специальным для театра процессом и прагматичной направленностью на сценическую деятельность. Между тем расширение и изменение, которое подходит к текстовым ссыкам, имеет целью появление и активизацию потоков и сохранения взаимосвязи между символами в преобразованных текстах.
Syniavska L. Text-Transforms – the Communicative Paradigm Basis of a Literary Work / L. Syniavska, V. Kolkutina, V. Pohrebennyk // WISDOM. – V. 15(2). – Khachatur Abovyan Armenian State Pedagogical University, 2020. – P. 56-67.
Keywords: artistic communication; communicative paradigm; text; text-transform; text-reference; художнє спілкування; комунікативна парадигма; текст; перетворення тексту; текст-посилання; художественное общение; коммуникативная парадигма; текст; преобразование текста; текст-ссылка; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Literature